Using the same fish with different rules: A science-based approach for improving management of recreational fisheries in a biodiversity hotspot of the Western South Atlantic - Garrone-Neto, Domingos [UNESP]; Sanches, Eduardo Antonio [UNESP]; Daros, Felippe Alexandre Lisboa de Miranda [UNESP]; Imanobu, Cleber Mikio Rosa [UNESP]; Moro, Pietro Simon (Wiley, 2018)
In this study we tested the hypothesis that Centropomus parallelus Poey moves between areas where fishing tourism is important, but the management rules for recreational fisheries are different. Fieldwork was conducted from May 2014 to June 2017 in an estuary located in the border between the states of São Paulo and Paraná, South-Southeastern Brazil. Through a mark and recapture experiment, 2.000 individuals were tagged, of which 42 were recaptured. Among these, six fish were recaptured in Paraná, after being tagged in São Paulo, and a fish was recaptured in São Paulo, after being tagged in Paraná. These results support the hypothesis tested and indicate an uneven use of C. parallelus by anglers in both states. Thus, the use of the species and the recreational fisheries regulations need to be reviewed in the study area, taking into account the ability of C. parallelus to move across political boundaries and the importance of a fish-oriented fisheries management regime.
Keywords: catch-and-release; Centropomidae; fisheries management; marine conservation; mark-and-recapture; sportfishing